2005
DOI: 10.1016/j.femsle.2005.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics ofOenococcus oenistrains in a new winery and the effect of SO2and yeast strain

Abstract: The effects of different yeast starters and SO(2) addition on malolactic fermentation in a new winery were evaluated by a molecular approach in three vintages. Alcoholic fermentations with 40 and 100mgl(-1) SO(2) were carried out, followed by uninoculated malolactic fermentations. Isolated colonies of Oenococcus oeni obtained from samples throughout the vinification were identified and typified by multiplex RAPD-PCR. This made it possible to monitor the population dynamics and follow the proportion of as many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 24 publications
4
23
1
1
Order By: Relevance
“…The frequency of participation of each genotype varied from year to year, thus dominant genotypes one year were minority or not present at other one which suggested the adaptation of Oenococcus oeni strains to the winery conditions every year. Similar results were reported by other authors in studies about bacteria and yeast populations (Gutierrez et al, 1999;Reguant et al, 2005a;Ruiz et al, 2010;Santamaría, 2009). …”
Section: Pfge Analysis Of the Strains Of This Studysupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency of participation of each genotype varied from year to year, thus dominant genotypes one year were minority or not present at other one which suggested the adaptation of Oenococcus oeni strains to the winery conditions every year. Similar results were reported by other authors in studies about bacteria and yeast populations (Gutierrez et al, 1999;Reguant et al, 2005a;Ruiz et al, 2010;Santamaría, 2009). …”
Section: Pfge Analysis Of the Strains Of This Studysupporting
confidence: 91%
“…fermentation could also influence, as it has been reported by other authors (du Plessis et al, 2004;Lonvaud-Funel, 1999;Reguant et al, 2005a;Reguant et al, 2005b). Figure 1 shows the number of isolates of the viable LAB species identified at each stage and year of vinification.…”
Section: Oenological Parameters Of Wine Samples and Fermentation Devementioning
confidence: 58%
“…Lurton et al (1989) have also reported the increase in nitrogen content during yeast autolysis in wines. The production of sulphur dioxide by inoculated commercial yeast was higher than in natural fermentation, but the content was too low to affect the growth of yeasts, or LAB (Würdig 1985;Reguant et al 2005). During the rapid development of fermentative yeasts, inhibition similarly peaked more quickly (Fig.…”
Section: Fermentation With Yeast Inoculationmentioning
confidence: 99%
“…Additionally, the content of molecular SO 2 at an amount of over 0.5 mg/l wine causes an inhibition of bacterial growth. In combination with other inhibitors, sulfur dioxide may at the same time limit the growth of bacteria and their ability for malic acid fermentation [24,55,56].…”
Section: Inhibition Of Bacteria O Oeni By Yeasts S Cerevisiaementioning
confidence: 99%